Call for Papers: Constitutions and Intergenerational Justice - IF and FRFG (Intergenerational Justice Review)
The Intergenerational Justice Review (IGJR) has been published by the Stuttgart-based think tank Foundation for the Rights of Future Generations (FRFG) since 2002. The 2012 edition was published in cooperation with the London-based Intergenerational Foundation (IF), and likewise the 2015 edition. For the latter as well as for the 2016 editions, the FRFG and IF have been joined by the University of Tübingen. The 2016 (2) edition will have the additional help of Professor Bruce Auerbach of Albright College, Reading PA, who will be serving as a guest editor.